Penerapan Disain Alternatif Pengembangan Rumah Adat Suku Dayak Tomun di Kabupaten Lamandau Provinsi Kalimantan Tengah: Penambahan Tempat Mandi-Cuci-dan Kakus (MCK) - Yophie Septiady; James Rilatupa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The Dayak Tomun tribe lives in traditional houses, which is related to bathing, washing, and latrine (BWL) problems. After the inventory is carried out, several aspects are then studied, both potential aspects and inhibiting aspects, by taking into account environmental factors, including the existence of surrounding natural resources. A potential aspect studied is the readiness and acceptance of the Dayak Tomun tribe in understanding aesthetics and health, related to BWL activities around their homes. The inhibiting aspect is the lack of facilities and knowledge about aesthetics and health. In the arrangement of the new floor plan, it is necessary to complete the feasibility of using the function of BWL rooms, sanitation facilities, clean water sources that are far from the river. The proposal for the development of this traditional house design, of course, considers the broad standards and circulation of space activities inside the house with activities in outdoor spaces resulting in space patterns that are more private, semi-public, and public. The use of non-organic building materials (steel and concrete) in traditional home repairs makes the physical existence of the building better. Meanwhile, with the existence of signs and customary cultural systems that have decreased in meaning, this can be avoided by preservation efforts, if the Housing and Settlement Office, and the Tourism Office make policies or regulations to maintain the design of traditional houses to continue to exist amid the rapid production of modern material products as building materials.